Sistem Pendukung Keputusan Pemilihan Leader Terbaik Menerapkan Menggunakan Metode Multi-Atribute Utility Theory (MAUT) - Sylvia Situmorang; Rima Tamara Aldisa (STMIK Budi Darma, 2024)
Leaders are people who have skills and strengths, including skills in a field, that can influence others to do certain jobs together to achieve a goal. A leader has an important role in influencing employee performance to increase the amount of profit the company can get. The process of selecting the best leader is one of the activities that must be carried out regularly by the company to improve the quality of its employees on an ongoing basis. Thus, the company needs a decision support system (SPK) in order to facilitate the company in carrying out the best leader selection activities in terms of time and obtaining more effective and efficient results. The method used by the author in this SPK is the Multi-Atribute Utility Theory (MAUT) method. The criteria used in this study are having the soul of a leader, high creativity, attractive appearance, loyalty, and having work experience in this field. The result of the Best Leader Selection research that deserves to be the best leader is alternative A3 with a final utility value of 1.2066058 on behalf of